Verification of an airframe fatigue life monitoring system using ex-service structure. (January 2018) - Molent, L.; Mau, V.
Abstract: In this paper the verification of the Royal Australian Air Force's (RAAF) F/A-18 Hornet Airframe Service Life Monitoring system is summarised. The availability of a significant number of RAAF ex-service centre fuselage sections with known usage facilitated this effort. Using an enhanced teardown procedure, in-service crack growth was identified at a significant number of locations. By comparing measured in-service growth with full scale fatigue test-demonstrated growth, and fitting failure distributions to the in-service data, the effectiveness of the monitoring system in maintaining a specific probability of failure was assessed. Highlights: Crack growth data from enhanced teardown of 7 ex-service aircraft components Components removed from service when life limits reached Allowed a verification of the ability of fatigue monitoring system to help maintain a required cumulative probably of failure level